Since this was so much fun, let's do it again. The sum is of the form for two integers and . Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = ( 1 + x ) 2 0 1 6 .
Let ω = i , the primitive fourth root of unity.
Thus it is easy to see that f ( 1 ) + f ( ω ) + f ( ω 2 ) + f ( ω 3 ) 2 2 0 1 6 + ( 1 + i ) 2 0 1 6 + ( 1 − i ) 2 0 1 6 2 2 0 1 6 + ( 2 i ) 1 0 0 8 + ( − 2 i ) 1 0 0 8 2 2 0 1 6 + 2 1 0 0 9 = 4 ∑ ( 4 k 2 0 1 6 ) + ( 1 + ω + ω 2 + ω 3 ) ∑ ( 4 k + 1 2 0 1 6 ) + ( 2 + 2 ω 2 ) ∑ ( 4 k + 2 2 0 1 6 ) + ( 1 + ω + ω 2 + ω 3 ) ∑ ( 4 k + 3 2 0 1 6 ) = 4 ∑ ( 4 k 2 0 1 6 ) = 4 P = 4 P = 4 P = 4 P ⟹ P = 2 2 0 1 4 + 2 1 0 0 7 ⟹ 2 0 1 4 + 1 0 0 7 = 3 0 2 1